2011
DOI: 10.1590/s1517-83822011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity, arbuscular mycorrhizal fungi and inoculation of woody plants in lead contaminated soil

Abstract: The goals of this study were to evaluate the microbial activity, arbuscular mycorrhizal fungi and inoculation of woody plants (Caesalpinia ferrea, Mimosa tenuiflora and Erythrina velutina) in lead contaminated soil from the semi-arid region of northeastern of Brazil (Belo Jardim, Pernambuco). Dilutions were prepared by adding lead contaminated soil (270 mg Kg-1) to uncontaminated soil (37 mg Pb Kg soil-1) in the proportions of 7.5%, 15%, and 30% (v:v). The increase of lead contamination in the soil negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Studies showed values of EE-BRSP that varied from 0.4 to 0.07 mg g soil −1 , together with an increase in the level of contamination with Cr. 45 The high levels of glomalin in Cerrado soil were probably represented by old stocks of this glycoprotein, since its stability and persistence in preserved environments can reach 42 years in tropical soils. 46 However, none of the treatments reached BRSP values similar to the 60 mg g soil −1 found in forest soils of temperate areas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed values of EE-BRSP that varied from 0.4 to 0.07 mg g soil −1 , together with an increase in the level of contamination with Cr. 45 The high levels of glomalin in Cerrado soil were probably represented by old stocks of this glycoprotein, since its stability and persistence in preserved environments can reach 42 years in tropical soils. 46 However, none of the treatments reached BRSP values similar to the 60 mg g soil −1 found in forest soils of temperate areas.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhization is beneficial to the host plant as it stimulates the growth of the seedlings (Machineski et al, 2009) and accumulates nutrients in the aerial parts (Ngwene et al, 2010), besides protecting the plant from pathogens (Elsen et al, 2008). The association between AMF and L. ferrea has been documented (Carneiro et al, 1998;Gattai et al, 2011), but now there is no information on the effects of mycorrhization on the production of secondary compounds. Recent studies have shown that mycorrhizal symbiosis, with its medicinal potential which can be an alternative for maximizing the production of chemical compounds (Ratti et al, 2010;Oliveira et al, 2013), with the produced phytomass having a higher concentration of active principles (Toussaint et al, 2007;Chaudary et al, 2008;Ratti et al, 2010;Ceccarelli et al, 2010;Dave and Tarafdar, 2011;Karagiannidis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are associated with representatives of more than 90% of the vascular plant families and, as obligate symbionts, are nutritionally dependent on the host plant (Smith & Read 2008). In exchange for plant-derived carbon, AMF facilitate plant absorption and uptake of nutrients from the soil, such as phosphorus (Jakobsen et al 2001), and can increase plants' tolerance to toxic elements (Cumming & Ning 2003;Gattai et al 2011), plant pathogens (Declerck et al 2002), saline stress (Yano-Melo et al 2003) and erosion (O'Dea 2007). The AMF can also help stabilize and aggregate soil, increasing the levels of soluble carbon and enzymes (e.g., urease, acid phosphatase and β-glucosidase), making them an important component to improve the growth of young plants under severe climate conditions (Caravaca et al 2002).…”
Section: Introductionmentioning
confidence: 99%